Pollen, tapetum and orbicule development in Modiolastrum malvifolium (Malvaceae) - Galati, B.G. (2007)
• Background and Aims: Although orbicular functions are still a matter of debate, they are considered by most authors to be exclusively formed by a secretory tapetum. However, the presence of orbicules on a peritapetal membrane associated with a plasmodial tapetum has been described for Abutilon pictum (Malvaceae) in a previous study. Thus, studies on other species of Malvaceae are necessary to corroborate the presence of such bodies in other members of the family. Pollen and microsporangium development of Modiolastrum malvifolium has been studied in this work. • Methods: Anthers at different stages of development were processed for transmission electron microscopy and light microscopy. Membranes and pollen walls resistant to acetolysis were isolated from whole anthers. • Key Results: Microspore tetrads have a tetrahedral arrangement. Pollen grains are shed at the bicellular stage. The tapetum is invasive, non-syncytial and a peritapetal membrane with orbicules is formed. • Conclusions: This is the first report of the presence of orbicules on a peritapetal membrane in a species with a tapetum of an invasive, non-syncytial type. Taking into consideration all the information on the subject, it can be concluded that the presence of orbicules is not a stable criterion to differentiate between a secretory or plasmodial, or intermediate invasive, non-syncytial tapetum. © The Author 2007. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.